2020
DOI: 10.1111/sjpe.12264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating strange forecasts: The curious case of football match scorelines

Abstract: This study analyses point forecasts of exact scoreline outcomes for football matches in the English Premier League. These forecasts were made for distinct competitions and originally judged differently. We compare these with implied probability forecasts using bookmaker odds and a crowd of tipsters, as well as point and probability forecasts generated from a statistical model. From evaluating these sources and types of forecast, using various methods, we argue that regression encompassing is the most appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Notable contributors to this research include Anders and Rotthoff (2011), Bar‐Eli, Tenenbaum, and Geister (2006), Carmichael and Thomas (2005), Chowdhury (2015), Cifuentes‐Faura (2022), Gasparetto, Mishchenko, and Zaitsev (2023), Gasquez and Royuela (2016), Gómez‐Déniz, Cárdenes, and Sánchez Pérez (2019), Greenberg (2015), Mattera (2023), Mechtel et al. (2011), Reade, Singleton, and Brown (2021), Titman et al. (2015), Turner, Meserve, and Bowen (2001), and Megía‐Cayuela 2023).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Notable contributors to this research include Anders and Rotthoff (2011), Bar‐Eli, Tenenbaum, and Geister (2006), Carmichael and Thomas (2005), Chowdhury (2015), Cifuentes‐Faura (2022), Gasparetto, Mishchenko, and Zaitsev (2023), Gasquez and Royuela (2016), Gómez‐Déniz, Cárdenes, and Sánchez Pérez (2019), Greenberg (2015), Mattera (2023), Mechtel et al. (2011), Reade, Singleton, and Brown (2021), Titman et al. (2015), Turner, Meserve, and Bowen (2001), and Megía‐Cayuela 2023).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The study findings indicate that the likelihood of winning while playing at home varies across different positions on the pitch, ranging from 41.99 percent for wide midfielders to 91.34 percent for center midfielders. Reade, Singleton, and Brown (2021) compared exact scoreline forecasts in the English Premier League with bookmaker odds, tipster crowds, and statistical models. They found that regression encompassing is the best method for comparing these forecasts, suggesting that both point and probability forecasts for match scorelines add valuable information.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The loss functions used in this work to evaluate the forecasts in this work are the Brier Score (BS, Brier 1950 ) and the log-loss. Further forecast evaluation methods in sports are discussed in Reade et al ( 2021 ). As in Angelini et al ( 2022 ) and Gorgi et al ( 2019 ), we use the Diebold and Mariano ( 1995 ) (DM) test to statistically assess the performance of the proposed model with respect to each competing specification.…”
Section: Empirical Analysismentioning
confidence: 99%
“…What is more, forecasts based on odds do not seem to perform worse than forecasts based on more elaborated statistical models (see Štrumbelj & Vračar, 2012; Forrest et al., 2005), although there is some work which has found the statistical models to be superior (see e.g. Reade et al., 2020).…”
Section: Full Rationalitymentioning
confidence: 99%